Wellbore stability analysis based on the combination of geomechanical and petrophysical studies - Abdolmanan Ounegh; Atefeh Hasan-Zadeh; Mohammad Mohammadi Khanaposhtani; Yousef Kazaemzadeh (Results in Engineering)
Determining the physical and mechanical properties of rocks is crucial for planning drilling operations. Ignoring geomechanical studies and tools has led to millions of dollars in additional costs related to drilling, meshwork optimization, production optimization, casing collapse, and other issues. These costs can be managed with a thorough geomechanical study. Additionally, some costs may not be apparent in the short term but will become significant over the life of the field. Long-term reservoir management is essential to control these costs. Issues such as reservoir compression, rock cover fractures, and gas storage, if neglected in the short term, can lead to substantial and irreparable damage to the reservoir over time. The ''geomechanical model'' is fundamental to geomechanical studies, particularly regarding wellbore stability. Given the importance of reservoir geomechanics and petrophysics, this research investigates wellbore stability analysis by combining geomechanical and petrophysical studies through the construction of a one-dimensional geomechanical model of the well. First, the dynamic geomechanical coefficients of the rock for the studied depth range were calculated from wells and petrophysical charts. Then, the static geomechanical coefficients of the rock were estimated based on laboratory-developed relationships. Subsequently, rock mechanics test results were used to estimate rock resistance parameters. The pore pressure was estimated using the compressibility and Eaton methods for the studied range from Well No. 5. Comparing the results of these two methods with RFT test data indicated that the compressibility method is more accurate than Eaton's method. By estimating the in situ and induced stresses in the well's studied area, the lower and upper limits of the safe mud weight were calculated using the Mohr-Coulomb and Hooke-Brown criteria. Comparison of the results showed that the Mohr-Coulomb criterion is more accurate and, moreover, more conservative than the Hooke-Brown method.